2022
DOI: 10.1111/and.14375
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline can reduce testicular apoptosis related to varicocele in male rats

Abstract: The current research aimed to assess the impacts of Minocycline on varicoceleinduced regulation of apoptotic-related genes and oxidative stress in the testis of adult Wistar rats. Thirty-two rats were divided into 4 groups: sham, varicocele (VcI), varicocele treated with Minocycline (VcI + Mno) for 56 days and healthy rats treated with minocycline (Mno). After 8 weeks, the oxidative stress markers levels in serum were investigated, afterwards, the level of Bax and Bcl-2 expression were assessed through 'immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Te testicular tissues and spermatozoa are very vulnerable to ROS attack and lipid peroxidation [8][9][10]. ROS produced by free fatty acids attack the cell membrane and cause damage to DNA and DNA fragmentation, which activates signaling pathways inducing testicular cell apoptosis [11][12][13]. Te fndings of the studies showed that ROS stimulated lipid peroxidation in the germ cell membrane and induced apoptosis in these cells [7,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Te testicular tissues and spermatozoa are very vulnerable to ROS attack and lipid peroxidation [8][9][10]. ROS produced by free fatty acids attack the cell membrane and cause damage to DNA and DNA fragmentation, which activates signaling pathways inducing testicular cell apoptosis [11][12][13]. Te fndings of the studies showed that ROS stimulated lipid peroxidation in the germ cell membrane and induced apoptosis in these cells [7,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, naturally occurring endogenous antioxidative systems (i.e., enzymatic and nonenzymatic antioxidants) protect against radiation‐induced oxidative damage by scavenging free radicals. Several studies have been reported on the association between antioxidant activity and testicular damages (Moghimian et al, 2017 ; Majid Shokoohi et al, 2022 ; Shokoohi et al, 2020 ; Soltani et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Following TT correction, more damage is done to the testicular tissue undergoing reperfusion injury than at the time of ischemia induction including tissue atrophy, disruption of seminiferous tubules, testosterone production reduction, fertility reduction, spermatogenesis reduction, and coagulative necrosis and disorganisation in germinal cell epithelium (Fehér & Bajory, 2016; Ünsal et al, 2006). Accumulation of ROS in ischemia/reperfusion (I/R) injury leads to DNA damage, lipid peroxidation, disorganisation in cell structure, protein coagulation, reduction in testosterone production, and activation of the germ cell apoptotic process (Shokoohi et al, 2020, 2022). Although the ischemic injury is an inevitable event, the complications of reperfusion should be prevented.…”
Section: Introductionmentioning
confidence: 99%